Acute and chronic changes of the apparent diffusion coefficient in neurological disorders: biophysical mechanisms and possible underlying histopathology - Gass, Achim; Niendorf, Thoralf; Hirsch, Jochen (Journal of the neurological sciences, 2001)
Diffusion-weighted imaging (DWI) of the brain has become a valuable tool for the reliable detection and diagnosis of several neurological disorders. Although DWI is in wide use in daily practice, the underlying biophysical mechanisms that contribute to changes in the apparent diffusion coefficient (ADC) are still under discussion. Alterations in the apparent water diffusion rate reflect pathological changes in the brain tissue state, via changes in the diffusion characteristics of the intra- and extra-cellular water compartments including restricted diffusion, water exchange across permeable boundaries, the concept of the extra-cellular tortuosity and the intra- and extra-cellular volume fraction. A reduction of the ADC has been detected in acute neurological diseases, while disease states associated with dominant acute vasogenic edema formation or chronic tissue destruction usually show elevations of the ADC. Compromise of energy metabolism is likely to contribute to a reduction of the ADC while already minor structural disintegration may contribute to elevations of the ADC.